Habermas and the therapeutic function of language - Pezdek, Krzysztof (Nursing philosophy, 2020)
The aim of this article was to interpret Habermas's concept of language in terms of its therapeutic potential which can be effectively realized in nursing practice. Drawing on Habermas's definition, we analyse the components of rational communication which are necessary for the patient and the therapist to achieve understanding. In doing this, we examine not only lifeworld, system and validity claims, which are well-known notions within Habermas's theory of communicative action, but also less frequently studied elements of this theory, such as everyday world, to which the patient refers in the process of self-understanding and identity construction. We also address culture and language as a pre-rational factor which can disturb, or even preclude, communication and understanding. In such circumstances, we propose supplementing the Habermasian therapeutic project with a psychoanalytical interpretations of the utterances of the patients who have difficulty defining the situation within which therapy is possible.